Induced breeding of endangered spiny eel (Mastacembelus armatus) using PG extract (Progressive Agriculture, 2018)
Mastacembelus armatus is an important freshwater spiny eel of Bangladesh. The experiment was initiated to establish an induced breeding technique of the species with two induced breeding trials. In trial I, four different doses viz. 20, 40, 60 and 80mg PGkg-1 body weight of the fish were used to standardize the PG dose to ovulate the female M. armatus, and in trial II, the best dose identified in trial I was injected to fish once (whole dose) or twice with divided dose of PG at the rate of 30% and 70% at 6h interval to observe the effect of the mode of hormonal injection. Among the four doses applied in trial I, best result was obtained from 40mg PGkg-1 body weight in respect of ovulation rate (100%) of females and fertilization (93.00±2.00%) and hatching rates (58.30±3.50%) of eggs. In trial II, the females treated once (with the whole dose) or twice with divided dose of PG equally responded and no significant difference (p>0.05) was observed between the modes of hormone injection in respect of ovulation rate of females and fertilization and hatching rates of eggs. As M. armatus is considered as endangered fish, this induced breeding technique will help to conserve the fish as well as to produce seed in commercial hatcheries.Progressive Agriculture 29 (3): 267-275, 2018